Perancangan Ulang Interior Perpustakaan Kabupaten Tangerang Dengan Pendekatan Perilaku - Putri Suwito, Intan; Puspa Nabila, Ganesha; Zulfia Budiono, Irwana (Telkom University, 2024)
There are a bunch of reasons why reading interest is low in Indonesia. Including a lack of activities that spark reading interest, limited reading materials, and low book sales. Because of this, the government really needs to focus on building facilities that match people's interests and prioritize social interactions. This is also true for the Tangerang Regency Library, which is trying to boost reading interest by making the library a hub for social interaction. The Tangerang Public Library is dealing with low reading interest and visitor numbers, especially among teens and adults, partly because of inadequate facilities and limited space. To tackle these issues, the library's interior needs a redesign to support activities like studying, discussing, and relaxing. By making better use of the space and improving security, these design changes are based on data from interviews, observations, field studies, and literature reviews to make sure everything meets the standards. Hopefully, this redesign will fit the community’s needs. Keywords: library, reading interst, redesign, Tangerang regency, visiting interst